Changes in the World Distribution of Output Per Worker, 1960–1998: How a Standard Decomposition Tells an Unorthodox Story - Beaudry, Paul; Collard, Fabrice; Green, David A. (The Review of Economics and Statistics, 2005)
Why have some countries done so much better than others over the recent past? This paper sheds light on this issue by providing a decomposition of the change in the distribution of output per worker across countries over the period 1960–1998. We find that most of the change in shape of the world distribution of income can be accounted for by a very substantial increase in the social returns to capital accumulation. In contrast, we do not find significant effects coming through changes in the effect of initial conditions or through increases in the importance of education.